Masked Multiple State Space Model Identification Using FRD and Evolutionary Optimization - Efe, Mehmet Onder; Kurkcu, Burak; Kasnakoglu, Cosku; Mohamed, Zaharuddin; Liu, Zhijie (IEEE transactions on industrial informatics, 2024)
Identification of dynamical systems from frequency response data (FRD) has extensively been studied and effective techniques have been developed. Given different FRD sets obtained from different systems and a fixed state space model structure, is it possible to find a constant parameter vector containing (A,B,C,D) quadruple's numerical content and a FRD-associated mask vector set that approximates the spectral information available in each FRD set? This article proposes a genetic algorithm based optimization approach to determine the real parameter vector (A,B,C,D) and the binary mask vector through a sequential optimization scheme. We study state space models for matching FRD from multiple systems. Results show that the proposed optimization approach solves the problem and compresses multiple dynamical models into a single masked one.